Floating Photovoltaic Potential in the Rawa Biru Area of South Papua Province - Johan Karim; Damis Hardiantono; Hariyanto Hariyanto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
National energy policy and renewable energy development policy towards 23% in 2025, the first target is to increase solar energy capacity as a priority where development includes rooftop solar power plants, large scale solar power plants, and floating solar power plants. The legal basis for the development of renewable energy is the policies of the central government and regional governments through regulations made. South Papua with the potential of Rawa Biru which is one of the sources of clean water in Merauke. Rawa Biru with a watershed area (DAS) of 4,791.671 km2 and an actual water body area of ​​95 ha. Simulation is done using Google Earth and Solargis software. Potential of floating PV in Rawa Biru with data maps, solar azimuth and PV configurations. Area of 95 ha floating PV potential 53,25 MWp, generating potential 79,93 GWh/year and area of 8 ha floating PV potential 2,14 MWp, generating potential 3,24 GWh/year.